Pengembangan Media PINTER (PowerPoint Interaktif) Berbasis Canva Untuk Meningkatkan Pemahaman Matematika pada Materi Bilangan Cacah - Addin Fikrullah Hidayat (Jurnal Pendidikan Matematika Undiksha, 2025)
This study aims to develop and evaluate PINTER (Interactive PowerPoint) media based on Canva as an interactive mathematics learning media for whole number material in elementary schools. The development model used is ADDIE (Analysis, Design, Development, Implementation, Evaluation) with a mixed method approach. The subjects of the study consisted of 20 fourth grade students of SDN Lidah Kulon I Surabaya. Data were collected through observation, interviews, questionnaires, and pre-tests and post-tests, then analyzed qualitatively and quantitatively. The results of validation by media and material experts showed that PINTER media was very feasible to use (feasibility score 92.5%). The use of this media increased student participation, motivation, and understanding. N-Gain analysis showed that 65% of participants experienced an increase in understanding in the moderate category, and 30% in the high category. The responses of students and teachers to the media were very positive, although technical challenges were found in the early stages of use. Overall, PINTER media based on Canva has proven to be effective and feasible as an alternative interactive learning media in elementary schools.